Universal Design and Orphan Technology: Do We Need Both? - Seelman, Katherine D. (Disability Studies Quarterly, 2005)
Implementation of Universal Design (UD) and availability of Orphan Technology (OT) have been recognized as challenges to governments and the marketplace, but indispensable to the realization of full citizenship for people with disabilities. The social dimensions of UD and OT have rarely been explored. This article selectively borrows from a transformational theory of technology (Feenberg, 2002) to explore technology transformation by assistive technology change agents. Change agents may harness the transformation potential of technology by involvement with factors internal to technology development such as design, technical codes and standards in order to realize the implementation of UD and availability of OT. They may also harness technology's potential by involvement in factors external to technology development such as attitudes, education, markets, and government incentives and mandates.